Analytical fracture parameters of two unequal collinear interface cracks in an orthotropic bimaterial - Tafreshi, Azam (Theoretical and applied fracture mechanics, 2022)
•Analytical SIF, Jk and COD of two unequal interface cracks in orthotropic bimaterials.•Analytical analysis of interface cracks in orthotropic or isotropic bimaterials.•Evaluation of fracture parameters of unequal interface cracks with elliptic integrals.•Effect of material mismatch and proximity of interface cracks on fracture parameters. This paper presents an analytical solution for the fracture parameters of two unequal collinear interface cracks (UCIC) in an infinite orthotropic or isotropic bimaterial subject to in-plane loading. The analytical expressions for the stress intensity factors (SIF), Jk-integrals and crack opening displacements of two UCIC in an infinite orthotropic bimaterial plate are derived using the complex variable method and evaluated in conjunction with the Jacobian elliptic functions and elliptic integrals. The presented theory is verified using the boundary element method. The results show that the fracture parameters are greatly influenced by mismatch of the engineering constants and proximity of the cracks. The inner tip of the longer crack always experiences the maximum SIFs and Jk values. These fracture parameters will increase exponentially when the distance between the cracks inner tips decreases. This study provides a baseline for the verification of future numerical and experimental studies of two UCIC which is not currently available in the SIFs handbooks.